Influence of parameters of PM controller on vibration performance of liquid hydrostatic guide-way system. (April 2018) - Chen, Liwen; Cui, Bingyan; Zhao, Jianhua; Gao, Dianrong
The vibration of liquid hydrostatic guide-way system during the working process makes a full impact on the machining precision of the numerically-controlled machine tool. The hydrostatic guide-way under the regulation of PM (Progressive Mengen) controller is taken as the research object. First, based on the force balance equation of hydrostatic guide-way, two kinds of vibration model of hydrostatic guide-way are established, respectively, and oil film stiffness equation and damping coefficient formula are derived. Second, the inherent frequency and amplitude of the guide-way system are derived. Third, the influence of PM controller parameters on the inherent frequency and amplitude of the guide-way system is analysed theoretically. The result indicates that the inherent frequency of the guide-way system changes with PM controller parameter and it makes a full impact on the active vibration amplitude of the hydrostatic guide-way system, but not the passive vibration amplitude. This article is provided a reference for the practical application of PM controller.